Análise da intensidade de carbono no setor de transporte rodoviário no Brasil - Costa, Mariane Gonzalez da (2019)
It is necessary the adoption of mitigation measures to achieve the Greenhouse Gas (GHG) reduction targets set by Brazil in the Paris agreement. From the developed method application for national context, this study aims to accomplish a historical analyze of Carbon Intensity (IC) and Energy Intensity (IE) of the transport sector, between 1990 and 2018, indicating which identified measures have a positive impact on CI and IE should remain and / or be improved to achieve those goals. The main measures identified were increasing the system’s energy efficiency and encouraging the use of alternative energy to fossil fuels. The impact of power generation and fuel production is analyzed by comparing life cycle CI with end use CI. Programs such as RenovaBio present the maintenance of the historically adopted measures and Rota 2030 seeks the rod transport Energy Efficiency improvement. However, by encouraging the use of biofuels, Brazil presents trends contrary to what occurs in developed and developing countries. Despite the Promob-e, program that seeks to encourage the standardization and regulation of electric vehicles, Brazil lags behind in fleet electrification compared to other countries. Thus, the survey of historical political factors allowed a critical evaluation of the measures historically adopted in Brazil, indicating which ones should remain and which one should be improved to broaden the results obtained.